2022
DOI: 10.1371/journal.pone.0271237
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccination uptake and its associated factors among adolescent school girls in Ambo town, Oromia region, Ethiopia, 2020

Abstract: Background The Human Papillomavirus (HPV) vaccine has offered a great promise to reduce the cervical cancer burden; its utilization (uptake) however has been lagging. However, the levels and factors associated with the uptake of the vaccine have not been well investigated, especially in the local context. Objective To assess the uptake of human papillomavirus vaccination and its associated factors among adolescent school girls in ambo town, Oromia, Ethiopia, 2020. Methods An institution-based cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 28 publications
6
28
0
Order By: Relevance
“…This is in line with research conducted in different parts of Ethiopia, including Ambo Town, Addis Ababa Town, and Gondar Town. [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with research conducted in different parts of Ethiopia, including Ambo Town, Addis Ababa Town, and Gondar Town. [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was prepared in the English language that was translated into Afaan Oromo and then translated back into English to check its consistency. The data collection tool has been adapted through a review of different pieces of literatures 3 and similar previous studies 9,11,16,24 . An eight‐part questionnaire was developed to assess sociodemographic characteristics, knowledge about CC, knowledge about HPV infection and vaccination, attitudes toward HPV vaccination, the presence of HPV vaccination advertisements, and source of information.…”
Section: Methodsmentioning
confidence: 99%
“…14 On the other hand, the acceptability of the HPV vaccine was affected largely due to unfavorable attitudes and beliefs toward the vaccine. 15,16 It was also shown that the reason for not being vaccinated was a delay, as well as a refusal based on the belief that vaccines were unnecessary. 17 These negative attitudes (hesitations) are not limited to those who refused vaccination but also to those who encourage others to refuse vaccination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Given the low uptake of human papillomavirus (HPV) vaccination among eligible women in Ethiopia, early determination of the precancerous lesion forms the foundation for the prevention and control of this important disease. 8,9 Besides, the utilization of cervical cancer screening service is very low in Ethiopia. 10 Hence, investigating the determinants of precancerous cervical lesion is useful to tailor more focused screening programs.…”
mentioning
confidence: 99%